Analisis Economic Value Added PT Garuda Indonesia (Persero) Tbk - Muhammad Rizal (Jurnal Serambi Ekonomi dan Bisnis, 2017)
This study aims to determine the financial performance. Garuda Indonesia Tbk by using Economic Value Added (EVA) during the period 2011 to 2015. The concept of Economic Value Added (EVA) measure a company's financial performance by taking into account the expectations of the funders and EVA is a measure that can stand on its own, does not require the existence of a comparison with similar companies in the industry. The data used in this study a financial statement data 2011-2015. Data analysis method used is the method of horizontal analysis, which compares the financial statements for some period of time. From the data analysis it can be seen that the calculation of EVA PT. Garuda  Indonesia (Persero) Tbk in 2011 to obtain the value of EVA respectively - Rp. 128 868 218 798, - USD. 164 386 022 040, - USD. 164 909 028 814, - USD. 632 771 636 094, and - Rp. 65,148,555,350. This shows that the management company has not been able to create a positive EVA or companies have not been able to create added value for its shareholders.